2003
DOI: 10.1038/nm825
|View full text |Cite
|
Sign up to set email alerts
|

The thrombomodulin–protein C system is essential for the maintenance of pregnancy

Abstract: Disruption of the mouse gene encoding the blood coagulation inhibitor thrombomodulin (Thbd) leads to embryonic lethality caused by an unknown defect in the placenta. We show that the abortion of thrombomodulin-deficient embryos is caused by tissue factor-initiated activation of the blood coagulation cascade at the feto-maternal interface. Activated coagulation factors induce cell death and growth inhibition of placental trophoblast cells by two distinct mechanisms. The death of giant trophoblast cells is cause… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
215
0
12

Year Published

2003
2003
2011
2011

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 245 publications
(229 citation statements)
references
References 45 publications
2
215
0
12
Order By: Relevance
“…Mouse trophoblast stem (TS) cells were obtained from J. Rossant (Hospital for Sick Children, Toronto, ON, Canada) and were maintained as stem cells or induced to differentiate as previously described (Isermann et al, 2003;Tanaka et al, 1998). Syncytiotrophoblast formation was monitored in nearly confluent TS cells differentiated for 6 days.…”
Section: Mouse Trophoblast Cell Culture and In Vitro Syncytium Formationmentioning
confidence: 99%
“…Mouse trophoblast stem (TS) cells were obtained from J. Rossant (Hospital for Sick Children, Toronto, ON, Canada) and were maintained as stem cells or induced to differentiate as previously described (Isermann et al, 2003;Tanaka et al, 1998). Syncytiotrophoblast formation was monitored in nearly confluent TS cells differentiated for 6 days.…”
Section: Mouse Trophoblast Cell Culture and In Vitro Syncytium Formationmentioning
confidence: 99%
“…1). The critical role of fibrin and fibrinogen degradation products in the maintenance of pregnancy is under investigation [8].…”
Section: Discussionmentioning
confidence: 99%
“…However, thrombomodulin-deficient mice, which lack the important natural anticoagulant protein C pathway, are unable to carry their fetuses beyond 8.5 weeks gestational age, and dead fetuses are usually resorbed within 24 hours. (12) Elegant experiments have shown that fetal demise is caused by tissue factor-dependent activation of blood coagulation at the feto-maternal interface. Activated coagulation factors were found to induce cell death and inhibit growth of trophoblast cells.…”
mentioning
confidence: 99%